Analysis of clay microstructure using scanning electron microscope and image analysis techniques - Dang Thi Minh Hue; Noppadol Phien-Wej; Pham, Huy Giao; Bergado, Dennes T.; Meer, Freek van Der; BRIDGE project Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Microfabric studies of soil have been enhanced by using Scanning electron microscopy (SEM). Through various techniques of image analysis, much research has been done to determine quantitative characteristics of geomorphology of soil microstructure. This research examines the changes in microstructure of clay at Hai Duong and Ha Dong sites in Vietnam due to shearing, consolidating and swelling. Samples that have undergone shearing the structure specimens exhibited face-to-face contact between particles. Consolidation pressure will create the closeness of particles contact. For sample that is affected by swelling, the structure is preserved. This study also reviewed the specimen preparation for microstructural observation in utilizing SEM by two methods: oven drying and critical point drying (CPD). From these results, it has been known that irrelevant permission of drying method may lead to incorrect understanding on the microstructure of clay soil
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Geotechnical and Geoenvironmental Engineering, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 2007
Keywords: Clay -- Microstructure; Image processing